2011
DOI: 10.1007/s10549-011-1845-z
|View full text |Cite
|
Sign up to set email alerts
|

High level of miR-21, miR-10b, and miR-31 expression in bilateral vs. unilateral breast carcinomas

Abstract: We analyzed the expression of several microRNAs (miRs) implicated in breast cancer (BC) pathogenesis (miR-21, miR-10b, miR17-5p, mir-31, miR-155, miR-200c, miR-18a, miR-205, and miR-27a) in 80 breast carcinomas obtained from patients with bilateral BC (biBC) and 40 cases of unilateral BC (uBC). Unexpectedly, three miRs (miR-21, miR-10b and miR-31) demonstrated significantly higher level of expression in biBC vs. uBC (P = 0.0001, 0.00004 and 0.0002, respectively). Increased contents of miR-21, miR-10b and miR-3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 48 publications
2
17
0
1
Order By: Relevance
“…MicroRNAs of the let-7 family were also reportedly down-regulated in several types of cancer [30]. We also found that miR-21-5p, the sole up-regulated miRNA in our list, was also previously found to be up-regulated [14,31]. However, changes in the expression of most of the miRNAs in our down-regulated list have not been reported in the literature.…”
Section: Resultssupporting
confidence: 61%
“…MicroRNAs of the let-7 family were also reportedly down-regulated in several types of cancer [30]. We also found that miR-21-5p, the sole up-regulated miRNA in our list, was also previously found to be up-regulated [14,31]. However, changes in the expression of most of the miRNAs in our down-regulated list have not been reported in the literature.…”
Section: Resultssupporting
confidence: 61%
“…Several recent studies have demonstrated that the expression of miR-27a is up-regulated in several types of solid tumors, including colon, gastric, cervical and breast cancers [10], [12], [24], [26]. The widespread overexpression of miR-27a in cancer has led to the belief that miR-27a is an oncogenic microRNA.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of next generation sequencing modalities has rapidly identified several miRNAs, including miR-205, miR-125b, miR-145, and miR-21, which are differentially expressed in breast carcinomas vs. normal breast tissue [102-104]. Interestingly, miR-21 binds to the 3’ untranslated region of CCL20 mRNA initiating its degradation [105].…”
Section: Ccl20 and Breast Cancermentioning
confidence: 99%